2022
DOI: 10.1111/jcpe.13623
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of the adjunct use of subgingival air‐polishing therapy with erythritol powder compared to conventional debridement alone during initial non‐surgical periodontal therapy

Abstract: Aim To assess the efficacy of the adjunct use of a subgingival erythritol powder air‐polishing device (EPAP) in comparison to conventional subgingival instrumentation alone during initial non‐surgical periodontal therapy. Materials and Methods Twenty‐one patients with generalized Stages 2 and 3 grade B periodontitis were included in this single centre, single blinded, split‐mouth, randomized clinical trial. Teeth on the control side were treated with conventional hand and ultrasonic instrumentation, while thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Both treatment methods significantly reduced periodontitis-related bacterial species, as well as BoP, PPD, and the relative attachment level. No significant differences were found between the various treatment methods [61].…”
Section: Differences In the Type Of Powdermentioning
confidence: 78%
See 1 more Smart Citation
“…Both treatment methods significantly reduced periodontitis-related bacterial species, as well as BoP, PPD, and the relative attachment level. No significant differences were found between the various treatment methods [61].…”
Section: Differences In the Type Of Powdermentioning
confidence: 78%
“…However, it may exert positive effects, such as reducing the frequency of residual periodontal pockets with a probing depth of 5 mm [60]. Resnik et al discovered that during the initial phase of non-surgical periodontal therapy, subgingival airflow therapy combined with an erythritol powder air-polishing device (EPAP) might benefit patients with initially deep pockets (probing pocket depth of 5.5 mm) [61]. Both treatment methods significantly reduced periodontitis-related bacterial species, as well as BoP, PPD, and the relative attachment level.…”
Section: Differences In the Type Of Powdermentioning
confidence: 99%
“…Furthermore, in the systematic review of Nascimento and coworkers [ 6 ], air-polishing showed no superior difference in comparison to SRP. Furthermore, a recent RCT published by Divnic-Resnik and coworkers concluded that EPAP could be efficient in reducing initial periodontal pockets with PD ≥ 5.5 mm [ 18 ]. On the other hand, the systematic review from Zhang and coworkers [ 19 ] concluded no efficiency of subgingival air-polishing compared to subgingival ultrasonic debridement during SPT.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Meanwhile, the surgical process would bring patients fear and discomfort. [ 3 ] As an alternative, antibiotics, such as minocycline, [ 4 ] metronidazole, [ 5 ] and tinidazole, [ 6 ] have shown promising potential in treating periodontitis. [ 7 ] Especially by simply adding these antibiotics to ointments and applying the resultant ointments to the target area, the release of antibiotics would kill the pathogens effectively, bringing about complete inflammatory eradication.…”
Section: Introductionmentioning
confidence: 99%